A just transition to climate-resilient economies and societies: issues and perspectives for the world of work (Geneva, 2016)
"This technical paper addresses the negative impacts of climate change on employment and livelihoods and explores how climate-related policy, investment and consumption responses to mitigate and adapt to the effects of climate change can affect labour markets in their entirety with overall job gains. It stresses the need of accompanying social and economic policies to achieve a just transition for all that leaves no one behind and promotes decent work."